Silat Pangian Hiliran Gumanti - Hirja Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to get an overview of traditional martial arts. Data were collected using participant observation, interview, and documentation study techniques. Informants were determined purposively by snowball sampling. The results showed that the traditional Pangian Silat came from Lintau, which was developed by Syeh Abdurrauf. The requirements that must be met to learn traditional Pangian martial arts are both limau (cutting liamau), Sirawa Tangguang item (black knickers that cover genitalia), stale rings (rings made of iron), Sabila knives (one-piece knives), limo shroud yard (five-yard shroud), pitch (Rp.25) adjusted to the present, Saiku rooster (one male rooster), and siriah langkok (Complete betel). The form of traditional Pangian martial arts movements or the characteristics of conventional Pangian martial arts, in general, will be seen in the slow gear and its nature to break the opponent's attack, gelek (hawk), steps, catches, and lock. While individually, it will be seen in pitunggu (horses), actions, strikes, sambuik, and Tangkok .Conclusions, traditional Pangian martial arts originated from Lintau which was developed by Syeh Abdurrauf, six conditions must be met to learn Pangian silat, the form of movement moves slow and its nature to break the opponent's attack, gelek (hawk), steps, catches, and locks Keywords: Silat Pangian Hiliran Gumanti